Cultural Barriers of Poverty Alleviation in the Microfinancing of Market Women in the Effutu Municipality of Ghana - Shirley Dankwa; Kwakye, Bio; Quartey, Robert; Eshun, Isaac (American Journal of Management, 2025)
This study explored three main aspects: the awareness of microfinance’s role, the barriers to accessing microfinance services, and the effects of microfinance on poverty alleviation among market women in the Effutu Municipality in the Central Region of Ghana. A qualitative approach and case study design were employed in this study. The population of the study was women traders in Effutu Municipality. Purposive and convenient sampling techniques were employed to select 15 participants. A semi-structured interview guide was the instrument used for data collection. Thematic analysis was used to analyze the data. The findings of this study were that while microfinance has the potential to enhance economic stability and improve the quality of life of market women, significant barriers such as difficulties in securing guarantors, delays in loan disbursements, and cumbersome repayment processes limit its effectiveness. It is recommended that microfinance institutions strengthen their outreach programs through partnerships with local radio stations, community leaders, and existing beneficiaries to spread awareness about the availability of their services and benefits.